2020
DOI: 10.1177/0032258x20962833
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the use of tactical officers in three Canadian police services

Abstract: In order to better understand the use of tactical police resources in Canada we interviewed patrol and tactical officers ( N = 28) from three Canadian police services. A thematic analysis indicated that tactical officers are primarily responding to calls beyond the capabilities of patrol to resolve optimally which included high-risk calls as denoted by the presence of risk-factors and calls unfolding in special environments. Further, tactical officer response is thought to result in a reduced threat to officer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Police and SWAT teams justify these practices by suggesting that risk and threat in society is growing each year, and thus policing with greater tactical use of weapons and strategies is required. In their article on the use of tactical officers in three Canadian police services, Jenkins and colleagues (2020) suggest much the same. Their argument is that regular duty police are not able to respond to most calls that are so-called high risk and that more and more calls involve such risk (p. 2).…”
Section: Introductionmentioning
confidence: 93%
“…Police and SWAT teams justify these practices by suggesting that risk and threat in society is growing each year, and thus policing with greater tactical use of weapons and strategies is required. In their article on the use of tactical officers in three Canadian police services, Jenkins and colleagues (2020) suggest much the same. Their argument is that regular duty police are not able to respond to most calls that are so-called high risk and that more and more calls involve such risk (p. 2).…”
Section: Introductionmentioning
confidence: 93%
“…Much of the Canadian scholarship on ERTs has focused on the normalization of ERTs in routine policing by tracking their annual deployments (Alvaro, 2000; Kraska, 2007; Roziere and Walby, 2018) Often, researchers highlight how the, arguable, normalization of militarization suggests that ERTs are taking on a more proactive policing role; for instance, executing warrant work, traffic enforcement, community-based policing initiatives, domestic disturbances and even mental health calls (ACLU, 2014; Roziere and Walby, 2018). However, recent scholars such as Jenkins et al (2020) challenge the assumption that police ERTs have become normalized. Rather, the use of ERTs can be expanded to understand that ERTs can be deployed to calls ‘beyond the capabilities of patrol to resolve optimally’, ‘reduce threat to officer and public safety’ or ‘to remove strain on general patrol’, suggesting a shift in resources as opposed to a normalization (Jenkins et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent scholars such as Jenkins et al (2020) challenge the assumption that police ERTs have become normalized. Rather, the use of ERTs can be expanded to understand that ERTs can be deployed to calls ‘beyond the capabilities of patrol to resolve optimally’, ‘reduce threat to officer and public safety’ or ‘to remove strain on general patrol’, suggesting a shift in resources as opposed to a normalization (Jenkins et al, 2020). This is a similar approach to that of den Heyer (2014) who also challenges the assumption that an increase in ERT call-outs is not an indication of militarization but rather ‘the rational utilization’ of expensive police resources (den Heyer, 2014: 354).…”
Section: Introductionmentioning
confidence: 99%
“…Interviews with tactical officers have indicated that they respond primarily to high-risk calls as indicated by the presence of these types of risk-factors (Jenkins et al, 2020;Rojek, 2005). However, we are not aware of studies that have relied on other sources of data to determine whether this is true.…”
Section: Introductionmentioning
confidence: 99%